Von despotischen Türken und kaltherzigen Deutschen: Zur Inszenierung und Destruktion kultureller Stereotype in der Komödie - Irrgang, Ulrike (Global Media Journal - German Edition, 2013)
This paper focuses on the cinematic representation of Turkish migrants and Germans in the two comedies Vatanyolu – Die Heimreise (1988) and Almanya - Willkommen in Deutschland (2011). In former movies Turkish characters were portrayed as the patriarchalic husband or father and the oppressed wife. The German society was represented as modern and civilised. The paper seeks to clarify the following questions: In which way are „the Germans“ and „the Turks“ characterized in Vatanyolu and Almanya? Is it possible to undermine stereotype representations by the use of humour? To answer these questions, firstly, the author shortly introduces the concepts of culture and cultural identity this article is based on. Then theoretical remarks on stereotypes are discussed as well as the potential of humour to subvert stereotypical representations. The analysis of the movie characters in Vatanyolu and Almanya shows that the filmmakers still use typical images of Turks and Germans. Although the family members in Vatanyolu are heterogeneous, the stereotypical representations can only be transcended in some cases. The characters in Almanya are more complex and multilayered, so the boundaries between „Turkish“ and „German“ disappear. In both movies stereotypes serve as basis for humour. Especially in Vatanyolu the commonly known images are simply reproduced by the filmmakers. However, in Almanya some jokes work against stereotypes by revealing their structure and logic.